Study of current trends in the labour market: changes caused by digital technologies and the COVID-19 pandemic - Suieubayeva, S.N.; Madiyarova, E.S.; Pestunova, G.B. (BUKETOV BUSINESS REVIEW, 2021)
Object: To study the current state and priorities of the labour market in the digital economy and the COVID-19 pandemic. Methods: The theoretical basis of the research is the work of domestic and foreign economists on the problems of the digitization of the labour market and the legislative and regulatory acts of the Republic of Kazakhstan. Data from the Statistical Committee of the Ministry of Economy of the Republic of Kazakhstan and the results of the authors' research have been compiled as an information base for the study. The methodological basis of the study is a systematic approach, abstract-logical, economical-statistical, monographic methods of studying economic processes. Findings: This article contains the results of an analysis of the labour market development of the Republic of Kazakhstan in comparison with foreign countries. Employment in the digital economy and the CORONA crisis are discussed. It is noted that the faster the digital economy is implemented, the more difficult it is to manage the digital economy. Technology is becoming not only an engine for the development of new industries, but also an important social role, making a significant contribution to the solution of societal problems such as population ageing, social stratification, environmental problems and climate change. With the help of advanced science and technology emerges a «smart» society based on new values oriented to the needs of the person, flexibility, creativity. As a result of digitization, the labour market, health care, education and spatial development are changing dramatically. Conclusions: The article discusses key aspects of the creation of conditions for the search for new forms of employment for the Kazakh economy from the standpoint of digitization. The emphasis is on the development of the digital environment in the modern environment. The content of state support of economic entities within the framework of the state program «Digital Kazakhstan» is considered. It was concluded that the changes brought about in the world economy by widespread restrictions in the context of the pandemic would lead to the search for new ways and forms of employment in the Kazakh labour market